The mechanism of formation of molecular conformations in ethylene glycol - Shermatov Abubakir; Temurova Elmira; Norbutayeva Iqboloy; Abduvohidov Sherzod; Elmurzayev Oybek (Global Scientific Publishing, 2023)
In this work, 4 different tTt, tGg', gTg' and gGg` conformations of the ethylene glycol (EG) molecule were studied using quantum chemical calculations and the method of B3LYP//6-311++G(d, p). Using the calculation, the optical and geometric parameters of the conformations were determined, and at the same time, the change in the shape of the O-H vibration band was analyzed in the conformations.
Keywords: Conformation; interaction energy; charge distribution